2022
DOI: 10.3390/ma15217561
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Effects of Nodular Cast Iron Laser Alloying with Selected Substances

Abstract: The aim of this research was to compare the effects of laser treatment, with the same heating conditions, using four selected alloying substances (silicon, cobalt, silicon nitride and titanium), in the surface layer of nodular cast iron. The treatment was performed with a molecular laser. As the microstructure observation revealed, the greatest amount of implemented elements was diluted during the treatment in a solid solution. In all cases (except during the alloying process with cobalt), in the alloying zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…A nearly threefold increment in the hardness of the surface layer was noted. Fourfold growth in hardness after titanium incorporation into nodular iron was noticed in the author's previous own research [18] although XRD did not indicate TiC in the surface layer. Near the surface, locally, only TiN or Ti(N,C) were visible in the microstructure as a result of interaction with nitrogen from the atmosfere.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…A nearly threefold increment in the hardness of the surface layer was noted. Fourfold growth in hardness after titanium incorporation into nodular iron was noticed in the author's previous own research [18] although XRD did not indicate TiC in the surface layer. Near the surface, locally, only TiN or Ti(N,C) were visible in the microstructure as a result of interaction with nitrogen from the atmosfere.…”
Section: Introductionmentioning
confidence: 72%
“…C The chromium as well as titanium was in the form of powder with a particle size of 325 mesh and 99.0% of purity. Those elements were chosen as the alloying elements for laser remelting also because of their ability to enrich the remelting zone during this treatment, which was confirmed during previous research [18,19] by EDS and AES analysis. After covering the surface, heating using a laser beam was conducted with a diode laser.…”
Section: Methodsmentioning
confidence: 83%
“…An approach to increase the hardness of GJS is laser heat treatment [7,8] or laser remelting [5,[9][10][11][12][13]. The laser remelting of metals involves the remelting of a thin surface layer, typically ranging from 1 to 100 µm, using laser radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness and other properties of laser-alloyed coatings have also been investigated [26][27][28][29][30][31][32]. Paczkowska [26] reported that the hardness of Si coatings was higher than that of the Ti, SiN and Co coatings at more than 900 HV 0.1 . Lont et al [27] found that titanium coatings can improve the surface hardness and erosion resistance of ductile iron.…”
Section: Introductionmentioning
confidence: 99%